Aeroponic Plant House System Using Direct Seeding in the Seedling Phase to Improve the Growth and Quality of Kangkung (Ipomoea aquatica Forssk.) - Prawiranegara, Boy Macklin Pareira; Sugandi, Wahyu Kristian; Akbar, Rafly Januar; Situmorang, Yogina Lestari Ayu (Jurnal Keteknikan Pertanian, 2023)
The purpose of this research is to analyze a plant house based aeroponic system using direct seed planting (tabela) during the seedling phase to demonstrate uniform growth and increase the production of water spinach (Ipomoea aquatica Forssk). The study was conducted at the Soil and Water Engineering Laboratory, Faculty of Agricultural Technology, Universitas Padjadjaran. The data collected included measurements of uniformity, survival rate, and production of water spinach (Ipomoea aquatica Forssk) during a 10-day observation period in February 2023. The study utilized a comparative-analytic method. The results of the study showed that the plant house method aeroponic system using direct seed planting is more efficient compared to the float system in terms of electricity usage, water usage, and energy cost. Additionally, the aeroponic system showed better growth uniformity in water spinach. Therefore, the plant house based aeroponic system using direct seed planting during the seedling phase can be an effective and efficient alternative for increasing the production of water spinach with uniform quality. The study concludes that this system is more effective and efficient in increasing the production of water spinach.